Pengelolaan Wakaf Produktif di Yayasan Rumah Sakit Islam (RSI) Surakarta - Dimas Reza Rifai (Falah: Jurnal Ekonomi Syariah, 2016)
The wealth in the Islamic perspective has an important roles to support the worship of human beings. Wealth is not the only goal, but one of the facilities for and provision to serve Allah. For human life in the world, one of the really matters is wealth, where wealth is all things owned a man, it has value and can be utilized for it to meet the life which included money used as the means of payment. Endowments have rooted in the Islamic community, and become supporter to the development Ummah. This can be seen on the fact that almost all of the worship, Islamic universities and religious Islamic institutions be built in land endowments.